Preliminary Pharmacogenetic Study to Explore Putative Dopaminergic Mechanisms of Antidepressant Action; Journal of Personalized Medicine; Vol. 11, iss. 8 - Ochi T. Taichi; Vyalova N. M. Nataljya Mikhaylovna; Losenkov I. S. Innokenty Sergeevich; Paderina D. Z. Diana; Pozhidaev I. V. Ivan Vyacheslavovich; Loonen A. J. M. Anton; Simutkin G. G. German Gennadjevich; Bokhan N. A. Nikolay Aleksandrovich; Wilffert B. Bob; Ivanova S. A. Svetlana Aleksandrovna (2021, 2021)
Title screen